Antigenic probes locate the myosin subfragment 1 interaction site on the N-terminal part of actin. Issue 5 (May 1986) - Méjean, C.; Boyer, M.; Labbé, J. P.; Derancourt, J.; Benyamin, Y.; Roustan, C.
Abstract : The interaction of two different anti-actin antibody populations with the myosin subfragment 1-F-actin rigor complex has been studied. In contrast with the 1–7 sequence, the 18–28 sequence appears to be strongly implicated in the contact area of the myosin head on the actin polypeptide chain.